2011
DOI: 10.1002/jor.21502
|View full text |Cite
|
Sign up to set email alerts
|

Localization of vascular endothelial growth factor during the early stages of osteochondral regeneration using a bioabsorbable synthetic polymer scaffold

Abstract: Vascular endothelial growth factor (VEGF) plays a critical role in chondrogenic differentiation in the growth plate of the epiphysis. This function is necessary for chondrocyte survival in cartilage development. We investigated the localization of VEGF in the osteochondral regeneration process using a bioabsorbable polymer scaffold. Osteochondral defects (5 mm in diameter and 5 mm in depth) were made on the femoral condyle of forty-eight skeletally mature female Japanese white rabbits. In total, twenty-four de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Previous chitosan-induced cartilage repair studies in rabbits have documented neutrophil chemotaxis at 21 days that is associated with a delay in matrix deposition, as observed in the current study [9,26]. The benefits of delayed matrix deposition after three weeks was also demonstrated in defects treated with PLG subchondral implants in rabbits, although implant clearance was not specifically reported and evidence of neutrophil or osteoclast attraction was not shown [3,27]. Most importantly, in a separate study, 10K pre-solidified chitosan-NaCl/blood implants elicited hyaline-like cartilage repair tissue and delayed callus formation compared to drill-only defects after 2.5 months in skeletally aged rabbits [28].…”
Section: Discussionsupporting
confidence: 71%
“…Previous chitosan-induced cartilage repair studies in rabbits have documented neutrophil chemotaxis at 21 days that is associated with a delay in matrix deposition, as observed in the current study [9,26]. The benefits of delayed matrix deposition after three weeks was also demonstrated in defects treated with PLG subchondral implants in rabbits, although implant clearance was not specifically reported and evidence of neutrophil or osteoclast attraction was not shown [3,27]. Most importantly, in a separate study, 10K pre-solidified chitosan-NaCl/blood implants elicited hyaline-like cartilage repair tissue and delayed callus formation compared to drill-only defects after 2.5 months in skeletally aged rabbits [28].…”
Section: Discussionsupporting
confidence: 71%
“…These results suggest that during osteochondral defect repair, robust tissue formation can be induced by promoting and inhibiting angiogenesis within the subchondral and chondral regions respectively. It is interesting to note that within a rabbit model, in osteochondral defects treated with a bioabsorbable scaffold which induced regeneration of the cartilage tissue in the superficial layer, the pro‐angiogenic factor VEGF was localized in the subchondral region of the defect . In the same study, in untreated defects VEGF was localized throughout the entire defect and no cartilage regeneration was observed …”
Section: Discussionmentioning
confidence: 84%
“…Bone overgrowth within osteochondral defects was shown to be promoted by growth factors such as transforming growth factor beta1 37 , or bone morphogenetic proteins 38 . In addition, angiogenesis promoted subchondral bone plate migration: Sakata et al 39 suggested that vascular endothelial growth factor might favour subchondral bone overgrowth in rabbits. Vice versa, the anti-angiogenic factors chondromodulin-I 40 and thrombospondin-1 38 , as expressed e.g., by implanted articular chondrocytes 41 , or other compounds 42 may prevent this inadvertent stimulation of osseous overgrowth.…”
Section: Discussionmentioning
confidence: 98%